Efektivitas Penerapan Metode Fishbowl Dalam Meningkatkan Hasil Belajar Peserta Didik Di SMK Negeri 4 Gowa - Hajar, Sitti; Lahming, Lahming; Ervi Novitasari (Jurnal Pendidikan Teknologi Pertanian, 2024)
The purpose of this study was to determine the improvement of learning outcomes of the basics of plant agribusiness with the implementation of the fishbowl method. The research method used is a quasi-experimental or quantitative approach. The type of test used is hypothesis testing (t-test), which first calculates the requirements of data analysis, namely normality test and homogeneity test. After analyzing the collected data, the average value obtained by experimental group students after the post test was 75.33. While the control group was 52.77. Data analysis used hypothesis testing and obtained a Sig. value in the experimental group of 0.901>0.05. Thus it can be concluded that the implementation of the fishbowl method on the learning outcomes of the basics of plant agribusiness is quite effective.